Living with the Enemy: Why High Priest Joseph Caiaphas was not a Roman Collaborator - Ryan, Maurice (Studies in Christian-Jewish Relations, 2022)
The term, collaborator, has been widely attributed to Jewish high priest Joseph Caiaphas when discussing his relationship with the Roman prefect Pontius Pilate. The implication of this description has been that Caiaphas holds ultimate responsibility for the execution of Jesus of Nazareth at the hands of the Romans. This article challenges the validity of the description of Caiaphas as a collaborator. Little evidence of any relationship between the two men exists. Likewise, any ability to see into the heart and mind of Caiaphas to assess motives and intentions is not available to modern investigations. The meaning of the word itself is malleable and has undergone shifts in usage since it was first applied to Caiaphas in the years immediately after the end of World War II. Assigning an unreliable term such as collaborator to Caiaphas is a stumbling block in relations between Christians and Jews.